2020
DOI: 10.1093/mnras/staa3277
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the impact of quasar luminosity on giant Ly α nebulae

Abstract: We present the results from a MUSE survey of twelve z ≃ 3.15 quasars, which were selected to be much fainter (20 < iSDSS < 23) than in previous studies of Giant Lyα Nebulae around the brightest quasars (16.6 < iAB < 18.7). We detect H I Lyα nebulae around 100% of our target quasars, with emission extending to scales of at least 60 physical kpc, and up to 190 pkpc. We explore correlations between properties of the nebulae and their host quasars, with the goal of connecting variations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 75 publications
4
35
1
Order By: Relevance
“…Our sample is compared in Fig. 4 to Lyα nebulae selected around QSOs, from Borisova et al (2016) and Mackenzie et al (2021). Their Lyα photo-ionization rates to L Lyα ratios are 1-2 orders of magnitude larger, on average, with respect to structures in our sample (Fig.…”
Section: Physical Interpretationmentioning
confidence: 74%
See 1 more Smart Citation
“…Our sample is compared in Fig. 4 to Lyα nebulae selected around QSOs, from Borisova et al (2016) and Mackenzie et al (2021). Their Lyα photo-ionization rates to L Lyα ratios are 1-2 orders of magnitude larger, on average, with respect to structures in our sample (Fig.…”
Section: Physical Interpretationmentioning
confidence: 74%
“…This is crucial for feeding even more massive galaxies (e.g., Daddi et al 2007) residing in massive halos at high redshifts (e.g., Bethermin et al 2014). Subsequent numerical and analytical modelling developed this theory with respect to stream stability (Nelson et al 2015;Mandelker et al 2019), multi-phase properties (Cornuault et al 2018), additional inner-halo cooling (Mandelker et al 2019(Mandelker et al , 2020Zinger et al 2018), angular momentum transfer to galaxies (Danovich et al 2015). This cold stream mode should be effective upto an evolving halo mass M stream (z), expected of order of 10 12.5 M at z = 2 and growing to 10 13.5 M at z = 3 (DB06), and rapidly diluted and disappearing at even higher masses.…”
Section: Introductionmentioning
confidence: 99%
“…Arrigoni showed that the luminosity of the Ly α extended emission possibly scales with the luminosity of the quasar. More recently Mackenzie et al (2021), by studying a large dynamic range in quasar luminosity, showed that the nebulae do get fainter near fainter quasars although the correlation is significantly sub-linear. As can be seen in Fig.…”
Section: The Radial Profile Of the Extended Ly α Emissionmentioning
confidence: 99%
“…The seminal papers by Rees (1988) and Haiman & Rees (2001), predicted that gas surrounding quasars reprocesses the impinging strong UV radiation as Ly𝛼 emission. Current studies routinely report extended Ly𝛼 emission, with ∼ 200 quasars surveyed to date at 2 < 𝑧 < 4 (e.g., Husband et al 2015;Fumagalli et al 2016;Borisova et al 2016;Arrigoni Battaia et al 2019a;Cai et al 2019;O'Sullivan et al 2020;Mackenzie et al 2021;Fossati et al 2021). The bulk of the extended emission traces gas on a few tens of kpc near the quasars, while large-scale structures extending to 𝑅 80 kpc are seen at lower surface brightness (SB Ly𝛼 ∼ 10 −18 erg s −1 cm −2 arcsec −2 ).…”
Section: Introductionmentioning
confidence: 99%